Adaptive Management: Learning and Action Approaches to Implementing Norms-shifting Interventions - McLarnon, Courtney; Gayles, Jennifer; Deepan, Prabu (USAID / Passages, 2021)
What Passages has Learned about Adaptive Management: • Be reflective about information that is collected and create a culture of learning. • Be systematic about establishing monitoring and learning systems. • Be strategic about data sources and analysis, prioritizing areas for learning and addressing issues raised. • Be inclusive about information collection: who is collecting what, how, and how is it being used.

Adaptive Programming and going with the grain: IMAGINE's new water governance model in Goma, DRC - Kirk, Tom; Green, Duncan; Stys, Patrycja; Mosquera, Tom (Development Policy Review, 2023)
Motivation This paper explores adaptive approaches to development programmes that aim at improving service provision in underperforming sectors in fragile and conflict affected states (FCAS). It does this through a case study of the Integrated Maji Infrastructure and Governance Initiative for eastern Democratic Republic of the Congo's (IMAGINE) public-private partnership model for water provision. Purpose The processes and decisions that culminated in IMAGINE's model emphasize the need for programming that is culturally and politically aware, responsive to events, learns in real-time, is entrepreneurial, and works with the grain of local institutions to support change. Detailed case studies of such ways of working are crucial for programmes that seek to challenge and reform the status quo in FCAS. Methods and approach The paper is based on 42 semi-structured interviews conducted in the summers of 2019 and 2020. They reflect the broad spectrum of actors – individuals, public authorities, and organisations – involved in IMAGINE's evolution. Findings The narrative focuses on IMAGINE's attempts to professionalise and commercialise Goma's water sector. It shows how as IMAGINE repeatedly adapted to ground realities, it took on the characteristics of a public authority, thereby, engendering backlashes that threated its longer-term goals. However, by revisiting its initial values and logics it was able to get things done and achieve it aims. Policy implications IMAGINE's story suggests that adaptive programmes should put politically savvy local development professionals in key positions and enable them to carefully construct coalitions of allies across the systems they aim to disrupt. This may also require them to revisit and adapt their initial ideas, guiding principles and values as greater understandings of development problems are gained. A pubic authorities lens, attuned to the logics programmes seek to address and introduce to FCAS, may help analysts to foreground the implications of such adaptations.

The Difference Learning Makes - Factors that enable and inhibit adaptive programming - Gray, Stephen; Carl, Andy (Christian Aid, 2022)
Executive Summary When Christian Aid (CA) Ireland devised its multi-country and multi-year Irish Aid funded Programme Grant II (2017-2022), they opted to move away from a linear programme management approach and to explore an adaptive one. Across seven countries: Angola, Colombia, El Salvador, Guatemala, Israel and the occupied Palestinian territory, Sierra Leone, and Zimbabwe, CA and partner organisations support marginalised communities to realise their rights, reduce violence and address gender inequality. Since 2019, Adapt Peacebuilding has accompanied CA Ireland, CA country teams and partner organisations as they experimented with using a deliberate adaptive approach. The authors were also asked to follow up on an initial study by CA Ireland and Overseas Development Institute in 2018, which described the rationale for adopting this new approach and included early lessons from its first year of implementation. The aim of this study is to help deepen CA Ireland, CA country teams’ and partners’ understanding of (a) whether their application of adaptive programming has resulted in better development outcomes, and (b) how they can better understand the factors that enabled or inhibited the effectiveness of using this approach. Over the past three years, this study has found evidence and multiple examples that show adaptive programming contributed to better development outcomes. The main reasons cited were that these were made possible both from improvements to programming strategies based on proactive reflection and learning, as well as those that stem from the reactive capacity of adaptive programmes to change course in response to unanticipated changes in operating conditions. This study found that adaptive programming has enabled better development practice where organisations are enhancing their skills to better respond and be flexible to contextual challenges. 72% of partners surveyed described adaptive programming as the most useful approach to programme management that they have used. The programme approach has meant that CA and partner staff were better able to explore the significance of change in the context and their contributions to them. It also enabled spaces for meaningful engagement with communities in learning and programme planning processes and encouraged opportunities for experimentation in programming. The study also found that adaptive programming has supported flexible delivery. This led to better outcomes that would not have been possible were the programme not able to make flexible adjustments. The main focus has been the analysis of nine factors that can determine the effectiveness and impact (or otherwise) of using an adaptive approach, flagging important issues for understanding. These factors are identified as: 1) Leadership; 2) Organisational culture; 3) Conceptual understanding; 4) Staff capacities; 5) Partnership approaches; 6) Participation; 7) Methods and tools; 8) Administrative procedures; and 9) The operating context. Together these can provide an analytical framework for assessing an organisation’s ‘adaptive scope’, which can be used as a tool for better understanding an organisation’s potential to generate improved development outcomes via adaptive programming and how to strengthen them. The study concludes with several recommendations for CA Ireland, all of which have relevance for a broader community of donors and implementing organisations interested in the potential of adaptive programming.

Pushing boundaries: Advocacy evaluation and real-time learning in an HIV prevention research advocacy coalition in sub-Saharan Africa - Dasmariñas, Jules; Schlangen, Rhonda (New Directions for Evaluation, 2021)
Evaluation processes that facilitate learning among advocates must be nimble, creative, and meaningful while transcending putative performance and accountability management. This article describes the experience, lessons, and trajectory of one such approach, Simple, Participatory Assessment of Real Change (SPARC), that a transnational HIV prevention research advocacy coalition pilot-tested in sub-Saharan Africa. Inspired by the pioneering work of the outcome harvesting (OH) and participatory evaluation community, we recuperate advocates' centrality as storytellers, sense-makers, and strategists in advocacy evaluation and describe how we recalibrated SPARC to meet their evaluation and learning needs. This article highlights the normative value of deliberative discourse in evaluation as it contributes to the interpretation of OH and the enrichment of the theory and practice of advocacy evaluation.